Acceptance of ring pessary in pelvic organ prolapse - Shrestha, Madhu (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aims: To evaluate the use of pessaries for women with Pelvic Organ Prolapse irrespectivve POP-Q stages. Method: This is retrospective study conducted at Paropakar maternity and Women’s hospital from mid April to mid December 2018 on 114 women with pelvic organ prolapse. Result: Total of 114 women with prolapse evaluated. Age of presentation ranged from 36 to 85 years. Twenty cases (17.6%) underwent prolapsed surgery and 71 cases (62.2%) had ring pessary. Conclusion: Overall acceptance of vaginal ring pessary is very high. It can be used in the majority of women with patient satisfaction and without noteworthy complication.